Autograft reconstruction of nasal dorsum in cutaneous neoplasia treatment - Camilla Siqueira de AGUIAR; Milena Mello Varela Ayres de Melo PINHEIRO; Rodrigo Henrique Mello Varela Ayres de MELO; Victor Leonardo Mello Varela Ayres de MELO; Lohana Maylane Aquino Correia de LIMA; Arnaldo de França CALDAS JÚNIOR; Ricardo Eugenio Varela Ayres de MELO (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Basal cell carcinoma is the most common type among skin cancers. It occurs in basal cells and is primarily caused by sun exposure. It mainly affects elderly people, mainly man, in exposed areas of the body and is diagnosed through biopsy. The choice of treatment depends on the type, size, location and depth of penetration, the patient's age, health conditions and potential aesthetic outcome. The present study aims to evidence, through a case report, the aesthetic and functional importance of the cutaneous transplant technique in cases of tissue loss in the face region by Basal cell carcinoma. A 56-year-old female patient, leukoderma, attended the Maxillofacial Surgery and Traumatology service of the Federal University of Pernambuco, complaining of asymmetry in the nasal dorsum region, with differentiated staining and raised edges. In anamnesis time she reported having suffered sun exposure for long periods. The patient underwent an incisional biopsy and subsequently, with a diagnosis of basal cell carcinoma, a resection of the lesion followed by skin autografting. Good acceptances of the skin flap as well as excellent aesthetic result were attained. The autogenous grafts use has shown satisfactory aesthetic results for remaining coverage after the lesion excision.